Effect of Naphthaleneacetic Acid (NAA) and 6-Benzylamino Purine (BAP) on In-Vitro Propagation of "Mashua" (Tropaeolum tuberosum Ruíz & Pavón) Morphotypes from Peru - Peña Rojas, Gilmar (2023)
Background: Tropaeolum tuberosum Ruız & Pavón “mashua” is a native species of the central Andes and different propagation methods in vitro have been evaluated. However, this research has studied the in vitro propagation of 15 mashua (Tropaeolum tuberosum Ruíz & Pavón) morphotypes from the Ayacucho and Apurímac regions (Peru) Objective: To evaluate the effect of the additives naphthaleneacetic acid (NAA) and 6-benzylamino purine (BAP) on the micro-propagation rate of T. tuberosum. Material and Methods: For in vitro establishment, seedlings were used after disinfection with sodium hypochlorite, propagated in Murashige and Skoog (MS) medium. For the evaluation of the effect of NAA and BAP additives, nodes were isolated from in vitro seedlings after 30 days of cultivation and transferred to MS medium supplemented with 3% sucrose, pH 5.6 and 7 g/L of agar according to T1 (MS + NAA 1ppm) and T2 (MS + BAP 1ppm) treatments. The samples were cultivated for 28 days at 19 °C ± 2 °C with photoperiods of 16 h/light and 8 h/darkness. Results: After evaluating 20 repetitions for each of the three treatments, the addition of NAA or BAP does not improve the micropropagation rate of practically all the morphotypes studied. Furthermore, BAP behaved as an inhibitor of the development of mashua seedlings. Conclusion: The best micropropagation medium of Tropaeolum tuberosum Ruíz & Pavón (mashua) is the basic Murashige and Skoog (MS) medium without the NAA or BAP additives.